The Changes of Consumer Psychology and Price Sensitivity in Uncertainty: A Case Study of Fast Fashion Brand ZARA - Sun, Yanjie (Transactions on Economics, Business and Management Research, 2024)
In recent years, there has been a collective decline in the development of fast fashion clothing brands in the Chinese market. Taking ZARA as an example, its parent company Inditex Group has undergone large-scale store adjustments globally in the past two years, especially in the Chinese market, where the number of ZARA stores has decreased by nearly half compared to four years ago. While Inditex's global revenue has grown, there has been a significant decline in revenue in mainland China. Therefore, understanding how the fast fashion industry was accepted by the Chinese market in the past and why it is now being excluded has gradually become important. For the clothing industry, market decision-making power has shifted from clothing merchants to consumers, and consumer psychology has undergone certain changes, and in fact, they have gained some bargaining power. As a product aimed at the general public, fast fashion brands have lower customer loyalty. Customers are more sensitive to price changes. In the rapidly changing and uncertain environment, the drawbacks of the fast fashion brand model have begun to emerge: convergent styles, unstable channels, and environmentally unfriendly production models, etc., which no longer have sufficient competitiveness in the current market. Therefore, this article intends to use literature research and case analysis methods for research, and to address the above issues, some suggestions are proposed, hoping to help fast fashion brands retain and expand the Chinese market.